Acoustic aspects of the speech of children - Rashmi M (Journal of All India Institute of Speech and Hearing, 1970)
Speech is a neuromuscular activity. In other words, the output of this activity is the acoustic signals, which are used for communication—as speech. The acousticcharacteristics of speech have been found to vary with age. These acoustic features on various aspects of speech production indicate that the accuracy of motor control improves with age until adult-like performance is achieved at about 11 or 12 years, somewhat after the age at which speech sound acquisition is usually judged to be complete.